Using WhatsApp Group in the Online English Learning Process at University During the Covid-19 Pandemic - Novarita, Novarita; Afifah, Nurul; Awalludin, Awalludin; Anam, Samsul; Noermanzah, Noermanzah (IJLECR (International Journal of Language Education and Cultural Review), 2023)
There are many benefits to using WhatsApp as a medium for distance learning, including the fact that it excites students about learning even from a distance and encourages concentration when using groups. However, in this current study, the usefulness of WhatsApp Groups in online learning during the Covid-19 pandemic of the English education study program at Baturaja University is investigated. The present writers utilized data gathered using a questionnaire and a Google Form as a bridge program. The results revealed that the benefits of WhatsApp media in the pandemic-related teaching and learning process WhatsApp makes it simple to send assignments, whether in the form of direct comments (chat groups), images, videos, PPTs, or other soft files, and features of. Moreover, the students enjoy learning activities. Out of all the replies respondents gave, most indicated that they would answer with the majority of statements they believed to be true for each item. This claims that during the COVID-19 Pandemic, using WhatsApp or creating WhatsApp Groups was incredibly helpful for their online learning process. The study's findings revealed that most participants thought that WhatsApp Groups are an effective medium.